Evaluation of Tensile Strength and Elongation of Bioplastic Films Manufactured from Cellulose of Local Amber Rice Husks Extracted by Chemical, Physical, and Biological Treatments - Abed, Eman H.; Abdulhay, Hind S.; Abbas, Adnan H. (Iraqi Journal of Science, 2026)
The use of bioplastics can be a promising option to achieve environmental sustainability and reduce environmental pollution, as it has a positive impact on reducing climate change and reducing greenhouse gas emissions compared to traditional plastics made from petrochemicals, which cause environmental pollution due to increased carbon dioxide emissions into the atmosphere as a result of burning and destruction of conventional plastics, which causes in major climate change due to rising temperatures and the occurrence of the global warming phenomenon. The high cellulose contents in Amber Rice Husk (ARH) support use as raw material for bioplastic synthesis and include the following components, cellulose 36.48%, hemicellulose 39.5%, lignin 7.14%, protein 1.09%, and ash 18.91%. This study aims to prepare a bioplastic film from chitosan, glycerin, sorbitol, and cellulose extracted from ARH using three chemical, physical, and biological processes, in addition to the measurement of the physical properties, such as tensile strength, and elongation. Three treatments (chemical, physical, and biological) were used in cellulose extraction from ARH to synthesize bioplastic films. The best treatment for cellulose production was the physical at a concentration of 61.05%, while chemical and biological treatments were 45.62, and 45.06%, respectively. The study primarily focuses on mechanical properties, such as tensile strength and elongation, essential for evaluating bioplastic usability in real-world applications. The result of tensile strength for the optimum bioplastic film, manufactured by chitosan (0.6, 0.8, and 1 g) and glycerol (2.0, 2.5, and 1.5 ml) added to the cellulose (0.8, 0.8, and 1 g) extracted by chemical, physical and biological treatments of the ARH respectively, proven that chemical and biological treatments (0.566 and 0.655 N/mm2), respectively, were slightly lower than physical treatment with (0.754 N/mm2), whereas, the elongation percentage of bioplastic film prepared by physical treatment was recorded at 20.44% lower than biological and chemical treatments at 28.66 and 24.42%, respectively.